OPTIMASI KUALITAS BRIKET BIOMASSA PADI DAN TONGKOL JAGUNG DENGAN VARIASI CAMPURAN SEBAGAI BAHAN BAKAR ALTERNATIF - Hamidah, Laily Noer; Rahmayanti, Ardhana (Journal of Research and Technology, 2017)
The energy crisis demands the development of an alternative energy that can meet daily needs. The existence of rice straw biomass waste and corn cob are potential to be utilized as bioenergy in the briquettes form. This research was conducted to develop and to test the characteristics of biomass briquettes as alternative fuels. Biomass used in this research is rice straw and corn cob. The making of briquettes is done through carbonation and compaction with 10% starch adhesive. To know the best quality of briquettes, a mixture of rice straw (100%) was used, mixed rice straw:corn cobs (25%:75%, 50%:50%, and 75%:25%), and corn cob (100 %). Test parameters used were ash content, volatile matter content, and calorific value. The results showed that briquettes from corn cobs were the best briquettes from ash content and volatile matter content of 9.52% and 9.7% respectively. While based on calorific value, briquettes with highest heating value was rice straw briquettes which was equal to 3562 Kcal/kg. Keywords: Biomass Briquette, Rice Straw, Corn cob, Ash Content, Volatile Matter, Calorific Value, Bioenergy.